Implementation of Demonstration Learning Strategies to Improve Fiqh Learning Achievement of Qurban Material in Grade V Students of MI Negeri X 2022/2023 - Nursyamsiah Nursyamsiah (Journal of Social Research, 2024)
This research is based on the following problems: (a) Does Demonstration Method Learning affect Fiqh learning achievement in Class V Students? (b) How high is the level of mastery of Fiqh subject matter with the application of the Demonstration Method Learning method to Class V students? The objectives of this study are: (a) To reveal the effect of Demonstration Method Learning on Fiqh learning achievement in Class V Students. (b) Want to know how far the understanding and mastery of Fiqh subjects after the application of Demonstration Method Learning in Class V Students. Each round consists of four stages: design, activity and observation, reflection, and reference. The target of this study is Class V students. The data obtained are in the form of formative test results, observation sheets of teaching and learning activities. From the results of the analysis, it was found that student learning achievement increased from cycle I to cycle III, namely, cycle I (68%), cycle II (78%), cycle III (100%). The conclusion of this study is that the Demonstration Method method can have a positive effect on learning motivation in Class V students, and this learning model can be used as an alternative to Fiqh Learning.